On dynamical systems induced by p-adic number fields - Ilwoo Cho (Opuscula Mathematica, 2015)
In this paper, we construct dynamical systems induced by \(p\)-adic number fields \(\mathbb{Q}_{p}\). We study the corresponding crossed product operator algebras induced by such dynamical systems. In particular, we are interested in structure theorems, and free distributional data of elements in the operator algebras.